2010
DOI: 10.3855/jidc.827
|View full text |Cite
|
Sign up to set email alerts
|

HCV and HIV prevalences strongly correlated in Asian communities with reservoirs of HIV in high-risk groups

Abstract: Background: In some Asian communities, HIV epidemics initially concentrated in high-risk groups develop into generalized epidemics, while in others HIV epidemics remain confined to high-risk groups. We examined whether blood exposures in a community, as indicated by hepatitis C virus (HCV) prevalence, can account for the variability in HIV prevalence in Asia. Methodology: We searched the published literature for temporally comparable HCV and HIV prevalence estimates for pregnant women and other "low-risk" popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The prevalence of blood-borne viruses was higher in PWIDs than in the general population, with prevalence of HIV among PWIDs at 18.4% to 29.5%, according to the national sentinel surveillance, 33,47 while other studies found the prevalence to be ranging from 17.5% to 72%. 18,47 –50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of blood-borne viruses was higher in PWIDs than in the general population, with prevalence of HIV among PWIDs at 18.4% to 29.5%, according to the national sentinel surveillance, 33,47 while other studies found the prevalence to be ranging from 17.5% to 72%. 18,47 –50…”
Section: Resultsmentioning
confidence: 99%
“…47 The prevalence of blood-borne viruses was higher in PWIDs than in the general population, with prevalence of HIV among PWIDs at 18.4% to 29.5%, according to the national sentinel surveillance, 33,47 while other studies found the prevalence to be ranging from 17.5% to 72%. 18,[47][48][49][50] Despite the shared modes of transmission of HIV, HBV, and HCV, the data show HBV prevalence among PWIDs similar to that in the general population. 18,21,22,23 This finding suggests that HBV infection most likely occurs in the early infant period.…”
Section: Situation In the Key Affected Populationsmentioning
confidence: 99%
“…7 This study however had only a small proportion of patients tested for HBV or HCV, and the presence of a coinfection in this study may have added to the high percentage of hepatotoxicity, as HIV-positive Asian communities were found to have a high prevalence of HCV. 13 cART in pregnant and non-pregnant womenCoinfection with HBV or HCV has been reported to be an independent risk factor for antiretroviral-associated hepatotoxicity, including NVP-related hepatotoxicity. 14 First, there could be enhanced toxicity of pre-existing HCV-or HBV-coinfection.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…The increase in patient survival numbers following the introduction of highly active antiretroviral therapy (HAART) has seen the emergence of HCV infection and chronic hepatic diseases as important morbidity and mortality causes together with HIV [2,3]. Similar transmission routes for HIV and HCV mean that coinfection is currently common, especially in injecting drug users and patients who have undergone blood transfusions, differing slightly from risk groups with isolated HIV or HCV [2,4,5]. It is estimated that 30% to 35% of HIV-infected patients in the United States of America are coinfected with HCV [2,6].…”
Section: Introductionmentioning
confidence: 99%